Cardiomyocyte-specific loss of RNA polymerase II subunit 5-mediating protein causes myocardial dysfunction and heart failure. Issue 11 (24th December 2018) - Zhang, Jian; Sheng, Jingyi; Dong, Liwei; Xu, Yinli; Yu, Liming; Liu, Yu; Huang, Xiaoru; Wan, Song; Lan, Hui-Yao; Wang, Huishan
Abstract: Aims: Myocardial dysfunction is an important cause of heart failure (HF). RNA polymerase II subunit 5 (RPB5)-mediating protein (RMP) is a transcriptional mediating protein which co-ordinates cellular processes including gene expression, metabolism, proliferation, and genome stability. However, its role in cardiac disease remains unknown. We aimed to determine the role and regulatory mechanisms of RMP in cardiomyocyte function and the development of HF. Methods and results: Myocardial RMP expression was examined in human heart tissues from healthy controls and patients with advanced HF. Compared to normal cardiac tissues, RMP levels were significantly decreased in the myocardium of patients with advanced HF. To investigate the role of RMP in cardiac function, Cre-loxP recombinase technology was used to generate tamoxifen-inducible cardiomyocyte-specific Rmp knockout mice. Unexpectedly, cardiomyocyte-specific deletion of Rmp in mice resulted in contractile dysfunction, cardiac dilatation, and fibrosis. Furthermore, the lifespan of cardiac-specific Rmp-deficient mice was significantly shortened when compared with littermates. Mechanistically, we found that chronic HF in Rmp-deficient mice was associated with impaired mitochondrial structure and function, which may be mediated via a transforming growth factor-β/Smad3-proliferator-activated receptor coactivator1α (PGC1α)-dependent mechanism. PGC1α overexpression partially rescued chronic HF in cardiomyocyte-specific Rmp-deficient mice, and Smad3 blockade protected against the loss of PGC1α and adenosine triphosphate content that was induced by silencing RMP in vitro . Conclusions: RMP plays a protective role in chronic HF. RMP may protect cardiomyocytes from injury by maintaining PGC1α-dependent mitochondrial biogenesis and function. The results from this study suggest that RMP may be a potential therapeutic agent for treating HF. Graphical Abstract: